No, the World is not Destined for War - Simkhada, Shambhu Ram (NCWA Annual Journal, 2023)
War is not a destiny; it is a human creation, a failure of politics, economics, diplomacy, and security policy. International Relations (IR) is the study of great power relations and how they affect the world. Understanding and conduct of contemporary IR based on old assumptions can be as erroneous and risky as concluding the inevitability of war between two 21st Century great powers based on what a scholar reminds us of the "Thucydides’ Trap", history of two warring Greek city-states because they could not accommodate each other’s national interests. What is Graham Ellison of Harvard’s Kennedy School, arguably one of the greatest global institutions of higher learning and powerhouses of ideas, trying to convey by characterizing 21st Century America-China relations by 5th Century BC Greek city-states? Do scholars and practitioners of IR realize the irony?